THE INFLUENCE OF COMMUNICATION, INDIVIDUAL CHARACTERISTICS AND RESPONSIBILITIES ON THE PERFORMANCE OF EMPLOYEES OF THE REGIONAL PLANNING, RESEARCH AND DEVELOPMENT AGENCY OF THE CITY OF PEMATANG SIANTAR - Siti Normi; Kristanty M N Nadapdap; Saur Melianna; Markus Doddy Simanjuntak; Angelina Sianipar (Fakultas Ekonomi Universitas Simalungun, 2025)
The purpose of this study is to determine and analyze the influence of communication, individual characteristics and responsibilities on the performance of employees of Bappeda Kota Daerah Kota Pematang Siantar. The type of data is quantitative data with a saturated sample of 42 respondents. Communication has a positive and partially significant effect on the performance of Bappeda Kota Pematang Siantar employees. Individual characteristics partially have a positive and significant effect on the performance of Bappeda Kota Pematang Siantar employees. Partial responsibility has a positive and significant effect on the performance of Bappeda employees in Pematang Siantar City. This study concluded that communication, individual characteristics, responsibilities simultaneously have a positive and significant effect on the performance of employees of the Regional Planning, Research and Development Agency of Pematang Siantar City